RELASI AGAMA DAN MANUSIA DALAM PEMIKIRAN MUHAMMAD IQBAL (Sebuah Tinjauan Filosofis Religius) - Junaidi Junaidi (Universitas Islam Negeri Imam Bonjol Padang, 2013)
The discussion about the relation between religion and human substantially depending on the perspective andunderstanding of the religion and the human themselves. First, it will indicate rationally directed creative inhuman beings, to give emphasis to individua of absolute self (ego). Secondly, with regard to human self-conceptof freedom and the immortality of the soul by emphasizing individu and human uniqueness. Muhammad Iqbalinsists on the fate of mankind as a unity of life. Studies on humans have not been exhaustively discussed inthe realm of thought. Even the issue and talks about people are always actual, sharp and covered up wheneverrelevant. Moreover, the terms of humanity always comes from thinkers with different perspectives and scientificareas of expertise under their control. The object of this research material is Iqbal’s thought about religion andhuman, and formal object is the discourse regarding the philosophy of religion. The method used in this studyis a hermeneutical method. The results showed that the self is more potential than actus. Potensia would be theactus of the whole process of self-actualization, and will end up in the context to be perfect man (Insan Kamil).